Teaching to learn Law - Rosa María Abdelnour Granados (Universitat Politècnica de València, 2014)
This article analyzes the necessity of a paradigm change in the way of how the process of teaching-learning the Law is approached, from a traditional, verbalism, discursive and with memorization requirements process to an active model, student centered, that lets him or her act in a competent way in the practice of Law and in life. It includes the change proposals: teachers training and curricula upgrade to adapt to the "New Normal" in a law career. It is necessary that the Law professional that teaches in a college, has received and receives training in teaching, according to the current guidelines in the area. It has been proven that it positively improves the teacher's performance; the current teaching approach in Law is not ideal because the graduates show difficulties to perform adequately; the professional practice faces them to events, problems, cases and their college teachers didn't teach them how to manage that, but only to take information in and reproduce it in a written test. Because of this, the conclusion is that it isn't enough to have a degree in Law to be trained to be teacher in this discipline. On top of the need to teach the academic staff and substitute the current way to approach the teaching and learning process, within that process, there has to be a career curricula upgrade, to include courses about topics, not only complementary to Law, but parallel to the traditional ones and therefore, not as optional but as main subject-matter: psychology, neuroscience, negotiation and conflict resolution, to mention the most relevant ones, according to the current development of the cognitive processes in the learning field.